Flectamus genua. Gonarthrosis in the Remains of the Blessed Giuseppe Benedetto Dusmet (Catania, Italy, 19th Century AD) - Piombino-Mascali, Dario; Grimaldi, Fausto; Liberto, Aldo; Ministeri, Federica; Privitera, Federico; Pomara, Cristoforo (Acta medica Lituanica, 2025)
Introduction: This study investigates the bioanthropological and paleopathological features of the late Blessed Giuseppe Benedetto Dusmet, a revered 19th-century archbishop of Catania. Dusmet’s remains were examined during the most recent canonical recognition in 2021, providing an opportunity to study the skeletal characteristics that may reflect his lifestyle and health.Materials and methods: Paleopathological analysis focused on degenerative changes using macroscopic inspection to identify osteoarthritic conditions. Historical records were also consulted to understand the potential connection between his devout religious practices and his physical health.Results: Significant degenerative and osteoarthritic changes were observed, particularly in the knees. These changes are hypothesized to be linked to Dusmet’s frequent practice of kneeling in prayer, a physical activity historically associated with knee osteoarthritis.Conclusion: This study highlights how bioanthropological and paleopathological analysis can provide insights into the health and lifestyle of historical figures. The observed knee osteoarthritis in the Blessed Giuseppe Benedetto Dusmet’s remains suggests a possible link between his behavior and the development of joint degeneration. This research adds to our understanding of the physical impact of religious practices and contributes to the study of health in historical figures.